Lethenteron ninae, a new nonparasitic lamprey species from the north-eastern Black Sea basin (Petromyzontiformes: Petromyzontidae) - Naseka, Alexander M.; Tuniyev, Sako B.; Renaud, Claude B. (Zootaxa, 2009)
Lethenteron ninae sp. n., a nonparasitic lamprey, is described from rivers of western Transcaucasia in Russia and Abkhazia. It is distinguished from the other species of Lampetrinae in Europe and west Asia (Black Sea basin) by the combination of the following character states: adults with a dark blotch near the apex of the second dorsal fin; exolaterals absent; posterials either absent or more commonly present in a single incomplete row of 3–7 teeth (a toothless gap in the middle); transverse lingual lamina with 9–15 unicuspid teeth, the median one markedly enlarged; supraoral lamina with two unicuspid teeth separated by a toothless bridge; 1–2 rows of anterials, usually 2; first row of anterials with 5–7 unicuspid teeth; oral fimbriae, 69–99; trunk myomeres in both ammocoetes and adults, 56–62; and in ammocoetes, trunk not mottled and tongue precursor bulb clearly triangular, with a wide base and a pointed apex bearing few cirri.